Management development: perceptions of change and problems of transfer - Drake, Jaqueline (Cranfield University, 1981)
Transfer of training, the concern of this thesis, is investigated in the context of a joint-venture in management development carried out by the Cranfield School of Management and Cable and Wireless Limited. Previous work in the. field of transfer - theoretical, experimental and empirical - is reviewed and relevant aspects incorporated into the study. The development of the joint-venture itself is explored in three contexts: business, educational and career. · The field study was conducted with the dual objectives of hypothesis testing and hypothesis generation. 181 ~ C & W managers participated in the general management~: programmes specially-prepared for them at Cranfield. Subsequently a questionnaire was sent to each of them at their place of work to elicit their perceptions of the programmes the influence of the organisational climate on their transfer efforts; and their transfer performance as it related to specific tasks and to their own end-of-programme resolutions. Findings suggest that, although the nature of-the learning experience and the organisational climate are undoubtedly important determinants of the. successful transfer of training~ the influence of both are modified substantially by· the type of manager. Perceptions are found to vary consistently with type of manager; "type" being defined by programme attended (a surrogate for "level"); Company categorisation of managers; work preferences, as identified by the Myers Briggs Type Indicator; age; professional background; and length of service with the Company. A model for the transfer of training is proposed, together with a number of practical recommendations for both parties to the joint-venture aimed at enhancing future management development activities. Availability of this thesis is at the discretion of the Steering Committee of the joint-venture.